A method for preparing a phthalate hydrogenation catalyst

By combining the modified silica support and Ni-Ru bimetallic active components, the activity and stability of the catalyst in the prior art under mild reaction conditions is solved, and the preparation of highly efficient and selective hydrogenation catalysts is achieved. , reducing precious metal loss and hydrogen costs.

CN116139876BActive Publication Date: 2025-02-25SINOPEC NANJING RES INST OF CHEM IND CO LTD +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202111391414.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-23
Publication Date
2025-02-25
Estimated Expiration
2041-11-23

AI Technical Summary

Technical Problem

Under relatively mild reaction conditions, it is difficult for the prior art to prepare hydrogenation catalysts with high activity, high selectivity and good stability, especially when the reaction pressure is low, the catalyst conversion rate is low and the selectivity is poor. Moreover, the precious metals have high loss rate and poor stability.

Method used

A preparation method is adopted, which involves mixing mesoporous silica with pretreated natural diatomaceous earth to form a modified silica support, and then adding Ru salt and Ni salt under stirring, by precipitation mixing and spraying The impregnation method uniformly distributes and adheres the active components to form a catalyst rich in Ni-Ru bimetallic active components.

Benefits of technology

The activity and stability of the catalyst are improved, the loss of precious metal Ru is reduced, the reduction activation time of the catalyst is shortened, the cost of hydrogen is reduced, and the efficiency of plasticizer production is improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for preparing a phthalate hydrogenation catalyst, which belongs to the field of catalytic technology. Mesoporous silica modified with diatomite is used as a carrier, and active component Ru and active component Ni are loaded on the modified carrier by a precipitation mixing method and a spray impregnation method, respectively, to obtain a finished catalyst. The phthalate hydrogenation catalyst prepared by the invention is used in a trickle bed reactor, has a short reduction activation time, high catalyst activity and good selectivity; and has no loss of precious metal Ru in the active component during long-term operation, and has good catalyst stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysis, and in particular to a method for preparing a phthalate hydrogenation catalyst. Background Art

[0002] Phthalates are widely used as plasticizers in children's toys, medical devices, food packaging, etc., and have always been in a dominant position in the industry. However, as people gradually pay more attention to life and environmental safety issues, people have found that phthalates can cause endocrine disorders in the human body, and long-term and large-scale intake can also lead to liver cancer. Therefore, the development and research of new, non-toxic, and environmentally friendly plasticizers has become the focus of attention. In the future, non-toxic cyclohexane 1,2-dicarboxylate will replace phthalates as the first choice of plasticizers in various fields, which also makes the research and development of cyclohexane 1,2-dicarboxylate produced by hydrogenation of phthalates a hot topic for scholars.

[0003] Patent US475064 describes the synthesis of cyclohexanedicarboxylic acid from phthalic acid using a 5% by mass Rh / C catalyst in the temperature range of 90-140°C. The content of Rh, a precious metal active component, is high, and the stability of the catalyst has not been reported. Chinese patent CN105056996A describes the synthesis of cyclohexanedicarboxylic acid from phthalic acid using a 1-5% by mass Ru catalyst at 80-150°C and a pressure of 3-5MPa. The reaction is an autoclave reaction, and it is difficult to separate the product from the catalyst after the reaction, and the loss of precious metals in the liquid phase reaction is serious. Chinese patent CN111036194A discloses a method for preparing a catalyst for the hydrogenation of phthalates, selecting at least one of Ru, Pd, Pt, Ag, Au, Ni, and Rh as an active component, and Al 2 O 3 、SiO 2 、ZrO 2 、TiO 2 、CeO 2 and one of the molecular sieves as carriers, under the conditions of reaction temperature of 180°C, reaction pressure of 8MPa, and hydrogen-ester ratio of 50 in a fixed bed reactor, the loss rate of precious metals is low, the stability is good, and the conversion rate and selectivity of the catalyst reach more than 99%, but the liquid space velocity value is not mentioned in the reaction conditions, and the stability data of the catalyst measured under what reaction load is unknown. Chinese patent CN106984310A discloses a method for preparing a phthalate hydrogenation catalyst, which uses precious metal Ru as an active component, and the carrier is one of zirconium oxide, magnesium oxide, silicon oxide or aluminum oxide, etc., and adopts an intermittent hydrogenation process. The catalyst needs to be reduced in a hydrogen atmosphere at 100~300°C for 3~10h, and the product yield is 99.49%. The reduction time is long, and the loss rate and stability of the precious metal are also unknown.

[0004] At present, in the hydrogenation of phthalates, the preparation of highly active, highly selective and stable hydrogenation catalysts under relatively mild reaction conditions is an important issue that researchers need to solve. Summary of the invention

[0005] 1. Technical problems to be solved:

[0006] In view of the above technical problems, the present invention provides a method for preparing a phthalate hydrogenation catalyst, which solves the problems of low catalyst conversion rate and poor selectivity under low reaction pressure; and solves the problems of high precious metal loss rate and poor catalyst stability during long-term operation.

[0007] 2. Technical solution:

[0008] A method for preparing a phthalate hydrogenation catalyst, characterized in that it comprises the following steps:

[0009] Step 1: dissolving mesoporous silica in water to prepare a suspension;

[0010] Step 2: Under stirring, add the pretreated natural diatomaceous earth to the suspension generated in step 1 for mixing and slurrying, then add alkali solution for neutralization and precipitation and adjust the pH value to 7.0-7.5;

[0011] Step 3: filtering and drying the material prepared in step 2 to obtain a modified silica carrier precursor;

[0012] Step 4: dissolving Ru salt in water to obtain a ruthenium salt solution with a Ru content of 0.001-0.01 g / ml, and adding the modified silica support precursor thereto under stirring for mixing and slurrying to obtain a catalyst precursor 1 rich in active component Ru;

[0013] Step 5: neutralize and precipitate the catalyst precursor 1 with an alkali solution and adjust the pH value to 7.5-8.0. The obtained material is then filtered, dried, roasted, crushed, and granulated to obtain a catalyst precursor 2 rich in active component Ru;

[0014] Step 6: Prepare a nickel salt solution with a Ni metal content of 0.05-0.1 g / ml, load it onto the surface of the catalyst precursor 2 by an equal volume spray impregnation method, and then dry and calcine to finally obtain a finished catalyst containing Ni-Ru bimetallic active components.

[0015] Furthermore, the specific surface area of ​​the mesoporous silica is 150-500 m 2 / g, pore size is 10~50nm.

[0016] Furthermore, the specific surface area of ​​the natural diatomaceous earth is 30-50m 2 / g, pore diameter of 10~1000nm, pore volume of 0.4~0.8cm 3 / g; the weight percentage content of Fe, Al, Mg, Ca metal oxides in the natural diatomite is Al 2 O 3 2.1~4.5%, Fe 2 O 3 It is 0.9~1.6%, MgO is 0.6~1.3%, and CaO is 0.7~1.4%.

[0017] Furthermore, the pretreatment in step 2 is to soak the natural diatomaceous earth in 1-5% dilute hydrochloric acid for 2-4 hours at a temperature of 20-40°C.

[0018] Furthermore, the mass ratio of the natural diatomaceous earth to the mesoporous silica is 1:(1-3).

[0019] Furthermore, the alkali solution is one of sodium hydroxide, sodium bicarbonate, sodium carbonate, potassium hydroxide, potassium carbonate, and potassium bicarbonate.

[0020] Furthermore, the Ru salt is ruthenium trichloride trihydrate, and the Ni salt is nickel nitrate hexahydrate;

[0021] Furthermore, the drying temperature in step three is 100~120°C, and the drying time is 2~4h; the drying temperature in step five is 120~150°C, and the drying time is 2~4h; the roasting temperature is 500~700°C, and the roasting time is 1~3h; the drying temperature in step six is ​​100~150°C, and the drying time is 2~4h; the roasting temperature is 400~550°C, and the roasting time is 1~3h.

[0022] Furthermore, in step 2, the stirring speed is 200-500 r / min, the temperature is 60-90° C., and the stirring time is 2-5 h.

[0023] Furthermore, in the finished catalyst containing the Ni-Ru bimetallic active component, the loading amount of the active component Ru is 0.1-1% of the weight of the finished catalyst, and the loading amount of the active component Ni is 3-8% of the weight of the finished catalyst.

[0024] 3. Beneficial effects:

[0025] (1) The mesoporous silica is modified by pre-treated diatomaceous earth, thereby enhancing the bonding between the silica carrier and the active component, making the catalyst have a good structure-activity relationship, thereby improving the activity and stability of the catalyst;

[0026] (2) The present invention uses Ni-Ru bimetallic as the active component, wherein the active component Ru is evenly distributed in the carrier by a precipitation mixing method, and has a high degree of bonding with the carrier, while the active component Ni is attached to the catalyst surface by a spray impregnation method to form a coating for the catalyst precursor. After the catalyst is used for a long time, the precious metal Ru does not lose and has good stability;

[0027] (3) The catalyst produced by the present invention has a short reduction activation time before use, which reduces the cost of hydrogen used in the reaction and shortens the plasticizer production cycle. DETAILED DESCRIPTION

[0028] The method of the present invention is described in detail below through examples, but the examples are only used to illustrate the invention and do not constitute a limitation on the scope of the present invention.

[0029] Example 1

[0030] 1) 10 g of natural diatomaceous earth was soaked in 1% dilute hydrochloric acid for 4 h, and the temperature was controlled at 30 ° C to obtain pretreated natural diatomaceous earth; 2) 30 g of mesoporous silica was dissolved in water to prepare a suspension; 3) The stirring speed was controlled to 200 r / min and the temperature was 60 ° C, and the pretreated natural diatomaceous earth was added to the above suspension for mixing and slurrying for 2 h, and then sodium bicarbonate solution was added thereto for neutralization and precipitation and the pH value was adjusted to 7.0; 4) The above materials were filtered and dried at 100 ° C for 4 h to obtain a modified silica carrier precursor; 5) Ru salt was dissolved in water to obtain a 0.001 g / ml (in terms of Ru metal) solution, and the stirring speed was controlled to 300 r / min and the temperature was 60 ° C, and the silica was added to the suspension for mixing and slurrying for 2 h. The silicon carrier precursor is added to the Ru salt solution and mixed and slurried for 2 hours to obtain a catalyst precursor 1 rich in the active component Ru; 6) The above catalyst precursor 1 is neutralized and precipitated with a sodium bicarbonate solution and the pH value is adjusted to 7.5; the obtained material is then filtered, dried at 120°C for 2 hours, calcined at 500°C, crushed, and granulated into 20 mesh to obtain a catalyst precursor 2 rich in the active component Ru; 7) 0.05g / ml (in terms of Ni metal) Ni salt solution is prepared, and it is loaded onto the surface of the catalyst precursor 2 by an equal volume spray impregnation method, and then dried at 150°C for 2 hours and calcined at 550°C for 1 hour to finally obtain a catalyst product I containing a bimetallic active component of 3% Ni-0.1% Ru.

[0031] Example 2

[0032] 1) 30g of natural diatomaceous earth was soaked in 5% dilute hydrochloric acid for 2h, and the temperature was controlled at 20°C to obtain pretreated natural diatomaceous earth; 2) 30g of mesoporous silica was dissolved in water to prepare a suspension; 3) The stirring speed was controlled to 500r / min and the temperature was 80°C, and the pretreated natural diatomaceous earth was added to the above suspension for mixing and slurrying for 3h, and then sodium carbonate solution was added thereto for neutralization and precipitation and the pH value was adjusted to 7.2; 4) The above material was filtered and dried at 120°C for 2h to obtain a modified silica carrier precursor; 5) Ru salt was dissolved in water to obtain a 0.01g / ml (in terms of Ru metal) solution, and the stirring speed was controlled to 600r / min and the temperature was 80°C, and the mesoporous silica was added to the above suspension for mixing and slurrying for 3h. The silicon dioxide carrier precursor is added to the Ru salt solution and mixed and slurried for 5 hours to obtain a catalyst precursor 1 rich in the active component Ru; 6) The above catalyst precursor 1 is neutralized and precipitated with a sodium carbonate solution and the pH value is adjusted to 7.5; the obtained material is then filtered, dried at 120°C for 2 hours, calcined at 500°C, crushed, and granulated into 10 mesh to obtain a catalyst precursor 2 rich in the active component Ru; 7) 0.1g / ml (in terms of Ni metal) Ni salt solution is prepared, and it is loaded onto the surface of the catalyst precursor 2 by an equal volume spray impregnation method, and then dried at 120°C for 3 hours and calcined at 450°C for 3 hours to finally obtain a catalyst product II containing a bimetallic active component of 8% Ni-1% Ru.

[0033] Example 3

[0034] 1) Soak 20g of natural diatomaceous earth in 3% dilute hydrochloric acid for 3h, and control the temperature at 30°C to obtain pretreated natural diatomaceous earth; 2) Dissolve 30g of mesoporous silica in water to prepare a suspension; 3) Control the stirring speed to 400r / min and the temperature to 90°C, add the pretreated natural diatomaceous earth to the above suspension for mixing and slurrying for 3h, and then add sodium hydroxide solution to neutralize and precipitate and adjust the pH value to 7.5; 4) Filter the above materials and dry them at 110°C for 2h to obtain a modified silica carrier precursor; 5) Dissolve Ru salt in water to obtain a 0.005g / ml (in terms of Ru metal) solution, and control the stirring speed to 500r / min and the temperature to 70°C, and add silica The carrier precursor is added to the Ru salt solution and mixed and slurried for 4 hours to obtain a catalyst precursor 1 rich in the active component Ru; 6) The above catalyst precursor 1 is neutralized and precipitated with a sodium hydroxide solution and the pH value is adjusted to 7.2; the obtained material is then filtered, dried at 140°C for 2 hours, calcined at 700°C for 2 hours, crushed, and granulated into 20 mesh to obtain a catalyst precursor 2 rich in the active component Ru; 7) 0.1g / ml (in terms of Ni metal) Ni salt solution is prepared, and it is loaded onto the surface of the catalyst precursor 2 by an equal volume spray impregnation method, and then dried at 150°C for 2 hours and calcined at 450°C for 2 hours to finally obtain a finished catalyst III containing a bimetallic active component of 8% Ni-0.5% Ru.

[0035] Example 4

[0036] 1) Soak 15g of natural diatomaceous earth in 2% dilute hydrochloric acid for 3h, and control the temperature at 35°C to obtain pretreated natural diatomaceous earth; 2) Dissolve 30g of mesoporous silica in water to prepare a suspension; 3) Control the stirring speed to 300r / min and the temperature to 70°C, add the pretreated natural diatomaceous earth to the above suspension for mixing and slurrying for 2h, and then add potassium hydroxide solution to neutralize and precipitate and adjust the pH value to 7.1; 4) Filter the above materials and dry them at 100°C for 4h to obtain a modified silica carrier precursor; 5) Dissolve Ru salt in water to obtain a 0.01g / ml (in terms of Ru metal) solution, and control the stirring speed to 500r / min and the temperature to 70°C, and add silica The carrier precursor is added to the Ru salt solution and mixed and slurried for 3 hours to obtain a catalyst precursor 1 rich in the active component Ru; 6) The above catalyst precursor 1 is neutralized and precipitated with potassium hydroxide solution and the pH value is adjusted to 7.2; the obtained material is then filtered, dried at 130°C for 3 hours, calcined at 650°C for 2 hours, crushed, and granulated into 25 mesh to obtain a catalyst precursor 2 rich in the active component Ru; 7) 0.05g / ml (in terms of Ni metal) Ni salt solution is prepared, and it is loaded onto the surface of the catalyst precursor 2 by an equal volume spray impregnation method, and then dried at 150°C for 2 hours and calcined at 400°C for 2 hours to finally obtain a catalyst product IV containing a bimetallic active component of 3% Ni-1% Ru.

[0037] Example 5

[0038] 1) Soak 25g of natural diatomaceous earth in 4% dilute hydrochloric acid for 4h, and control the temperature at 30°C to obtain pretreated natural diatomaceous earth; 2) Dissolve 30g of mesoporous silica in water to prepare a suspension; 3) Control the stirring speed to 500r / min and the temperature to 60°C, add the pretreated natural diatomaceous earth to the above suspension for mixing and slurrying for 3h, and then add potassium bicarbonate solution to neutralize and precipitate and adjust the pH value to 7.2; 4) Filter the above materials and dry them at 110°C for 3h to obtain a modified silica carrier precursor; 5) Dissolve Ru salt in water to obtain a 0.003g / ml (in terms of Ru metal) solution, and control the stirring speed to 500r / min and the temperature to 60°C, and add silica The carrier precursor is added to the Ru salt solution and mixed and slurried for 5 hours to obtain a catalyst precursor 1 rich in the active component Ru; 6) The above catalyst precursor 1 is neutralized and precipitated with potassium bicarbonate solution and the pH value is adjusted to 7.4; the obtained material is then filtered, dried at 120°C for 4 hours, calcined at 650°C for 2 hours, crushed, and granulated into 25 mesh to obtain a catalyst precursor 2 rich in the active component Ru; 7) 0.07g / ml (in terms of Ni metal) Ni salt solution is prepared, and it is loaded onto the surface of the catalyst precursor 2 by an equal volume spray impregnation method, and then dried at 140°C for 3 hours and calcined at 450°C for 2 hours to finally obtain a catalyst product V containing a bimetallic active component of 5% Ni-0.3% Ru.

[0039] Example 6

[0040] 1) Soak 17g of natural diatomaceous earth in 2% dilute hydrochloric acid for 2h, and control the temperature at 30°C to obtain pretreated natural diatomaceous earth; 2) Dissolve 30g of mesoporous silica in water to prepare a suspension; 3) Control the stirring speed to 350r / min and the temperature to 70°C, add the pretreated natural diatomaceous earth to the above suspension for mixing and slurrying for 4h, and then add potassium carbonate solution to neutralize and precipitate and adjust the pH value to 7.0; 4) Filter the above materials and dry them at 105°C for 3h to obtain a modified silica carrier precursor; 5) Dissolve Ru salt in water to obtain a 0.008g / ml (in terms of Ru metal) solution, and control the stirring speed to 450r / min and the temperature to 60°C, and add silica The carrier precursor is added to the Ru salt solution and mixed and slurried for 4 hours to obtain a catalyst precursor 1 rich in the active component Ru; 6) The above catalyst precursor 1 is neutralized and precipitated with potassium carbonate solution and the pH value is adjusted to 7.1; the obtained material is then filtered, dried at 140°C for 3 hours, calcined at 650°C for 2 hours, crushed, and granulated into 20 mesh to obtain a catalyst precursor 2 rich in the active component Ru; 7) 0.06g / ml (in terms of Ni metal) Ni salt solution is prepared, and it is loaded onto the surface of the catalyst precursor 2 by an equal volume spray impregnation method, and then dried at 130°C for 2 hours and calcined at 450°C for 2 hours to finally obtain a catalyst product VI containing a bimetallic active component of 4% Ni-0.8% Ru.

[0041] Example 7

[0042] 1) Soak 17g of natural diatomaceous earth in 2% dilute hydrochloric acid for 2h, and control the temperature at 30°C to obtain pretreated natural diatomaceous earth; 2) Dissolve 30g of mesoporous silica in water to prepare a suspension; 3) Control the stirring speed to 450r / min and the temperature to 80°C, add the pretreated natural diatomaceous earth to the above suspension for mixing and slurrying for 4h, and then add potassium carbonate solution to neutralize and precipitate and adjust the pH value to 7.2; 4) Filter the above materials and dry them at 105°C for 3h to obtain a modified silica carrier precursor; 5) Dissolve Ru salt in water to obtain a 0.005g / ml (in terms of Ru metal) solution, and control the stirring speed to 400r / min and the temperature to 60°C, and add silica The carrier precursor is added to the Ru salt solution and mixed and slurried for 3 hours to obtain a catalyst precursor 1 rich in the active component Ru; 6) The above catalyst precursor 1 is neutralized and precipitated with potassium carbonate solution and the pH value is adjusted to 7.2; the obtained material is then filtered, dried at 140°C for 3 hours, calcined at 700°C for 2 hours, crushed, and granulated into 20 mesh to obtain a catalyst precursor 2 rich in the active component Ru; 7) 0.06g / ml (in terms of Ni metal) Ni salt solution is prepared, and it is loaded onto the surface of the catalyst precursor 2 by an equal volume spray impregnation method, and then dried at 130°C for 2 hours and calcined at 450°C for 2 hours to finally obtain a finished catalyst product VII containing a bimetallic active component of 4% Ni-0.5% Ru.

[0043] Example 8

[0044] 1) Soak 17g of natural diatomaceous earth in 2% dilute hydrochloric acid for 2h, and control the temperature at 30°C to obtain pretreated natural diatomaceous earth; 2) Dissolve 30g of mesoporous silica in water to prepare a suspension; 3) Control the stirring speed to 450r / min and the temperature to 80°C, add the pretreated natural diatomaceous earth to the above suspension for mixing and slurrying for 4h, and then add potassium carbonate solution to neutralize and precipitate and adjust the pH value to 7.2; 4) Filter the above materials and dry them at 115°C for 2h to obtain a modified silica carrier precursor; 5) Dissolve Ru salt in water to obtain a 0.008g / ml (in terms of Ru metal) solution, and control the stirring speed to 400r / min and the temperature to 60°C, and add silica The carrier precursor is added to the Ru salt solution and mixed and slurried for 3 hours to obtain a catalyst precursor 1 rich in the active component Ru; 6) The above catalyst precursor 1 is neutralized and precipitated with potassium carbonate solution and the pH value is adjusted to 7.3; the obtained material is then filtered, dried at 150°C for 3 hours, calcined at 650°C for 2 hours, crushed, and granulated into 25 mesh to obtain a catalyst precursor 2 rich in the active component Ru; 7) 0.08g / ml (in terms of Ni metal) Ni salt solution is prepared, and it is loaded onto the surface of the catalyst precursor 2 by an equal volume spray impregnation method, and then dried at 130°C for 2 hours and calcined at 550°C for 1 hour to finally obtain a finished catalyst product VIII containing a bimetallic active component of 6% Ni-0.8% Ru.

[0045] Example 9

[0046] 1) Soak 30g of natural diatomaceous earth in 3% dilute hydrochloric acid for 2h, and control the temperature at 30°C to obtain pretreated natural diatomaceous earth; 2) Dissolve 30g of mesoporous silica in water to prepare a suspension; 3) Control the stirring speed to 550r / min and the temperature to 70°C, add the pretreated natural diatomaceous earth to the above suspension for mixing and slurrying for 3h, and then add sodium bicarbonate solution to neutralize and precipitate and adjust the pH value to 7.2; 4) Filter the above materials and dry them at 115°C for 2h to obtain a modified silica carrier precursor; 5) Dissolve Ru salt in water to obtain a 0.001g / ml (in terms of Ru metal) solution, and control the stirring speed to 400r / min and the temperature to 60°C, and add silica The carrier precursor is added to the Ru salt solution and mixed and slurried for 3 hours to obtain a catalyst precursor 1 rich in the active component Ru; 6) The above catalyst precursor 1 is neutralized and precipitated with a sodium bicarbonate solution and the pH value is adjusted to 7.5; the obtained material is then filtered, dried at 150°C for 3 hours, calcined at 600°C for 2 hours, crushed, and granulated into 25 mesh to obtain a catalyst precursor 2 rich in the active component Ru; 7) 0.1g / ml (in terms of Ni metal) Ni salt solution is prepared, and it is loaded onto the surface of the catalyst precursor 2 by an equal volume spray impregnation method, and then dried at 130°C for 2 hours and calcined at 550°C for 1 hour to finally obtain a finished catalyst product IX containing a bimetallic active component of 8% Ni-0.1% Ru.

[0047] Comparative Example 1

[0048] 1) Dissolve Ru salt in water to obtain a 0.01 g / ml (in terms of Ru metal) solution; 2) Dissolve 30 g of mesoporous silica in water to prepare a suspension, and control the stirring speed to 400 r / min and the temperature to 60°C, add the above Ru salt solution and mix and slurry for 3 hours to obtain a catalyst precursor 1 rich in active component Ru; 3) Use sodium bicarbonate solution to neutralize and precipitate the above catalyst precursor 1 and adjust the pH value to 7.0; the obtained material is then filtered, dried at 130°C for 3 hours, calcined at 600°C for 2 hours, crushed, and granulated into 25 mesh to obtain a catalyst precursor 2 rich in active component Ru; 4) Prepare a 0.05 g / ml (in terms of Ni metal) Ni salt solution, load it onto the surface of the catalyst precursor 2 by an equal volume spray impregnation method, and then dry it at 130°C for 2 hours and calcine it at 550°C for 1 hour to finally obtain a catalyst product A containing a bimetallic active component of 3% Ni-1% Ru.

[0049] Comparative Example 2

[0050] 1) Dissolve Ru salt in water to obtain a 0.01 g / ml (in terms of Ru metal) solution; 2) Dissolve 30 g of natural diatomaceous earth in water to prepare a suspension, and control the stirring speed to 400 r / min and the temperature to 60°C, add the above Ru salt solution and mix and slurry for 3 hours to obtain a catalyst precursor 1 rich in active component Ru; 3) Use sodium bicarbonate solution to neutralize and precipitate the above catalyst precursor 1 and adjust the pH value to 7.0; the obtained material is then filtered, dried at 120°C for 4 hours, calcined at 600°C for 2 hours, crushed, and granulated into 25 mesh to obtain a catalyst precursor 2 rich in active component Ru; 4) Prepare a 0.1 g / ml (in terms of Ni metal) Ni salt solution, load it onto the surface of the catalyst precursor 2 by an equal volume spray impregnation method, and then dry it at 130°C for 2 hours and calcine it at 550°C for 1 hour to finally obtain a catalyst product B containing a bimetallic active component of 8% Ni-1% Ru.

[0051] Comparative Example 3

[0052] 1) 50 g of mesoporous silica and 3 g of cellulose were kneaded, dried at 110°C for 2 h, and granulated into 20 mesh to obtain a silica carrier; 2) 0.001 g / ml (in terms of Ru metal) Ru salt solution was prepared, the above carrier was immersed in it for 2 h, and dried at 120°C for 2 h to obtain a catalyst precursor 1; 3) 0.05 g / ml (in terms of Ni metal) Ni salt solution was prepared, the above catalyst precursor 1 was immersed in it for 2 h, dried at 120°C for 2 h, and calcined at 450°C for 2 h, finally obtaining a finished catalyst C containing a bimetallic active component of 3% Ni-0.1% Ru.

[0053] Comparative Example 4

[0054] 1) 50 g of mesoporous silica and 3 g of cellulose were kneaded, dried at 110°C for 2 h, and granulated into 20 mesh to obtain a silica carrier; 2) 0.001 g / ml (in terms of Ru metal) Ru salt solution was prepared, the above carrier was immersed in it for 2 h, dried at 120°C for 2 h, and calcined at 450°C for 2 h, and finally a catalyst product D containing 0.1% of active component Ru was obtained.

[0055] Comparative Example 5

[0056] 1) 50 g of mesoporous silica and 3 g of cellulose were kneaded, dried at 110°C for 2 h, and granulated into 20 mesh to obtain a silica carrier; 2) 0.05 g / ml (in terms of Ni metal) Ni salt solution was prepared, the above carrier was impregnated therein for 2 h, dried at 120°C for 2 h, and calcined at 450°C for 2 h, and finally a catalyst product E containing 3% of active component Ni was obtained.

[0057] Catalyst performance evaluation

[0058] Catalysts I to IX and Comparative Examples A to E were loaded into a trickle bed reactor and reduced at 250°C under a 0.5 MPa hydrogen atmosphere for 1 h. The reaction temperature was 180°C, and the hydrogen pressures were 7.0 MPa, H 2 The molar ratio of phthalates is 50, and the liquid space velocity of phthalates is 0.2h -1 and 0.6h -1 , sampling and analysis were carried out after reaction time of 100h and 500h.

[0059] .

[0060] It can be seen from the reaction data in the table that the catalysts I to IX prepared by this method have a high reaction temperature of 180°C, a reaction pressure of 7.0 MPa, and H 2 Under the condition of ester / ester molar ratio of 50, regardless of the liquid space velocity of 0.2h -1 Still 0.6h -1 , 500h all showed good DINP conversion rate and DINCH selectivity, and the stability was guaranteed; while comparative examples A~E showed good conversion rate and selectivity at the initial stage of the reaction, but their conversion rate and selectivity decreased significantly after 500h of reaction, and the stability was poor. Therefore, after the reaction, the used catalysts I~IX and comparative examples A~E were subjected to physical and chemical analysis, and the results showed that there was no loss of precious metal Ru in the catalyst prepared by the method of this patent, while the loss rate of precious metal in comparative examples A~E was 0.3~0.5ppm%.

[0061] Although the present invention has been disclosed as above in terms of preferred embodiments, they are not intended to limit the present invention. Anyone skilled in the art can make various changes or modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the scope of protection defined by the claims of this application.

Claims

1. A method for preparing a phthalate hydrogenation catalyst, characterized in that: The following steps are involved: Step 1: dissolving mesoporous silica in water to prepare a suspension; Step 2: Under stirring, add the pretreated natural diatomaceous earth to the suspension generated in step 1 for mixing and slurrying, then add alkali solution for neutralization and precipitation and adjust the pH value to 7.0-7.5; Step 3: filtering and drying the material prepared in step 2 to obtain a modified silica carrier precursor; Step 4: dissolving Ru salt in water to obtain a ruthenium salt solution with a Ru content of 0.001-0.01 g / ml, and adding the modified silica support precursor thereto under stirring for mixing and slurrying to obtain a catalyst precursor 1 rich in active component Ru; Step 5: neutralize and precipitate the catalyst precursor 1 with an alkali solution and adjust the pH value to 7.5-8.

0. The obtained material is then filtered, dried, roasted, crushed, and granulated to obtain a catalyst precursor 2 rich in active component Ru; Step 6: Prepare a nickel salt solution with a Ni metal content of 0.05-0.1 g / ml, load it onto the surface of the catalyst precursor 2 by an equal volume spray impregnation method, and then dry and calcine to finally obtain a finished catalyst containing Ni-Ru bimetallic active components; The pretreatment in step 2 is to soak the natural diatomaceous earth in 1-5% dilute hydrochloric acid for 2-4 hours at a temperature of 20-40°C; The mass ratio of the natural diatomaceous earth to the mesoporous silica is 1:(1-3); The loading amount of the active component Ru in the finished catalyst containing the Ni-Ru bimetallic active component is 0.1-1% of the weight of the finished catalyst, and the loading amount of the active component Ni is 3-8% of the weight of the finished catalyst.

2. A method for preparing a phthalate hydrogenation catalyst according to claim 1, characterized in that: The specific surface area of ​​the mesoporous silica is 150-500 m 2 / g, pore size is 10~50nm.

3. The method for preparing a phthalate hydrogenation catalyst according to claim 1, characterized in that: The specific surface area of ​​the natural diatomaceous earth is 30-50m 2 / g, pore diameter of 10~1000nm, pore volume of 0.4~0.8cm 3 / g; the weight percentage contents of Fe, Al, Mg and Ca metal oxides in the natural diatomite are 2.1-4.5% for Al2O3, 0.9-1.6% for Fe2O3, 0.6-1.3% for MgO and 0.7-1.4% for CaO, respectively.

4. The method for preparing a phthalate hydrogenation catalyst according to claim 1, characterized in that: The alkali solution is one of sodium hydroxide, sodium bicarbonate, sodium carbonate, potassium hydroxide, potassium carbonate and potassium bicarbonate.

5. The method for preparing a phthalate hydrogenation catalyst according to claim 1, characterized in that: The Ru salt is ruthenium trichloride trihydrate, and the Ni salt is nickel nitrate hexahydrate.

6. The method for preparing a phthalate hydrogenation catalyst according to claim 1, characterized in that: The drying temperature in step three is 100~120℃, and the drying time is 2~4h; the drying temperature in step five is 120~150℃, and the drying time is 2~4h; the roasting temperature is 500~700℃, and the roasting time is 1~3h; the drying temperature in step six is ​​100~150℃, and the drying time is 2~4h; the roasting temperature is 400~550℃, and the roasting time is 1~3h.

7. The method for preparing a phthalate hydrogenation catalyst according to claim 1, characterized in that: The stirring speed in step 2 is 200~500r / min, the temperature is 60~90℃, and the stirring time is 2~5h.

Citation Information

Patent Citations

  • Catalyst for selectively hydrogenating dimethyl terephthalate to prepare 1,4-cyclohexane dimethyl isophthalate and preparation method and use method of catalyst

    CN105056996A

  • Preparation method of catalyst for phthalate hydrogenation

    CN111036194A

  • Watch-case pendant

    US475064A

  • Phthalate type plasticizer hydrogenated catalyst preparation method thereof and application

    CN106984310A